An In Vitro Evaluation of Denture Cleansing Regimens against a Polymicrobial Denture Biofilm Model - Jason L. Brown; Tracy Young; Emily McKloud; Mark C. Butcher; David Bradshaw; Jonathan R. Pratten; Gordon Ramage (MDPI AG, 2022)
Denture stomatitis (DS) is an inflammatory disease resulting from a polymicrobial biofilm perturbation at the denture surface-palatal mucosa interface. Recommendations made by dental health care professionals often lack clarity for appropriate denture cleaning. This study investigated the efficacy of brushing with off-the-shelf denture cleanser (DC) tablets (Poligrip®) vs. two toothpastes (Colgate® and Crest®) in alleviating the viable microorganisms (bacteria and fungi) in an in vitro denture biofilm model. Biofilms were grown on poly(methyl)methacrylate (PMMA) discs, then treated daily for 7 days with mechanical disruption (brushing), plus Poligrip® DC, Colgate® or Crest® toothpastes. Weekly treatment with Poligrip® DC on day 7 only was compared to daily modalities. All treatment parameters were processed to determine viable colony forming units for bacteria and fungi using the Miles and Misra technique, and imaged by confocal laser scanning microscopy (CLSM). Brushing with daily DC therapy was the most effective treatment in reducing the viable biofilm over 7 days of treatment. Brushing only was ineffective in controlling the viable bioburden, which was confirmed by CLSM imaging. This data indicates that regular cleansing of PMMA with DC was best for polymicrobial biofilms.